2020
DOI: 10.3168/jds.2019-17085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-nitrooxypropanol on rumen fermentation, lactational performance, and resumption of ovarian cyclicity in dairy cows

Abstract: This study examined the effect of 3-nitrooxypropanol (3-NOP), a substance under investigation, on enteric methane (CH 4 ) emission, rumen fermentation, lactational performance, sensory properties of milk, and the resumption of ovarian cyclicity in early-lactation dairy cows. Fifty-six multi-and primiparous Holstein cows, including 8 that were rumen cannulated, were used in a 15-wk randomized complete block design experiment. Cows were blocked based on parity and previous lactation milk yield (MY) or predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
132
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(166 citation statements)
references
References 96 publications
(176 reference statements)
28
132
6
Order By: Relevance
“…This was explained by the decreased acetate to propionate ratio reflecting a shift from H 2 liberating to H 2 consuming fermentation pathways and the potential redirection of excessive H 2 from inhibited methanogenesis to alternative sinks. The present experiment confirmed that both 3-NOP and the readily degradable carbohydrates in HC diets decreased the molar proportions of acetate (Van Kessel and Russell 1996;Lopes et al 2016) but increased that of propionate, butyrate and valerate (Haisan et al 2014;Lopes et al 2016;Melgar et al 2020) which are thermodynamically favourable for H 2 disposal (Morgavi et al 2010). Additionally, the deamination of branched-chain amino acids could have been affected as iso-valerate increased due to 3-NOP supplementation.…”
Section: Changes In Rumen Fermentation Variablessupporting
confidence: 79%
See 2 more Smart Citations
“…This was explained by the decreased acetate to propionate ratio reflecting a shift from H 2 liberating to H 2 consuming fermentation pathways and the potential redirection of excessive H 2 from inhibited methanogenesis to alternative sinks. The present experiment confirmed that both 3-NOP and the readily degradable carbohydrates in HC diets decreased the molar proportions of acetate (Van Kessel and Russell 1996;Lopes et al 2016) but increased that of propionate, butyrate and valerate (Haisan et al 2014;Lopes et al 2016;Melgar et al 2020) which are thermodynamically favourable for H 2 disposal (Morgavi et al 2010). Additionally, the deamination of branched-chain amino acids could have been affected as iso-valerate increased due to 3-NOP supplementation.…”
Section: Changes In Rumen Fermentation Variablessupporting
confidence: 79%
“…In contrast, in our trial, antimethanogenic effects of 3-NOP were identified to be transient in NOP LC group (70% forages). This could be related to the notably higher dietary aNDFom content of approximately 400 g/kg in NOP LC and 340 g in NOP HC group, respectively, ( Table 2) when compared to 276 g of NDF/kg DM (Hristov et al 2015b) and 318 g of NDF/kg DM (Melgar et al 2020). In a meta-analytical approach, Dijkstra et al (2018) identified that the 3-NOP effect on CH 4 yield decline was impaired by 1.52 ± 0.41% per 10 g/kg DM increase of dietary NDF content in dairy cattle.…”
Section: Effects Of Diet Composition and 3-nop On Methane Emissionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same calculation conducted with NADH oxidation occurring through electron confurcation would yield a considerable higher range of dissolved H 2 concentration between 6 and 100 µM, again assuming equilibrium between gaseous and aqueous H 2 . Therefore, with electron confurcation, the range of dissolved H 2 concentration at which NADH oxidation becomes thermodynamically controlled coincides or is even higher than previously reported peaks of dissolved H 2 concentration after feed ingestion, or the dissolved H 2 concentration reported by Melgar et al (2019) for methanogenesis inhibition (Table 1). This agrees with the findings by Greening et al (2019) regarding the importance of confurcating hydrogenases in H 2 formation in the rumen.…”
Section: Effects Of Dihydrogen Accumulation On the Rates Of Fermentatsupporting
confidence: 56%
“…Pathways of [H] flow alternative to H 2 formation can result in the production of other intercellular e − carriers, such as lactate, ethanol, and formate, or final fermentation products such as propionate, all of which also help NADH oxidation (Van Lingen et al, 2016). Formate, succinate or ethanol have been shown to accumulate along with H 2 when methanogenesis was inhibited in vitro (Slyter, 1979;Asanuma et al, 1998;Ungerfeld et al, 2003) and in vivo (Martinez-Fernandez et al, 2016, 2017Melgar et al, 2019), so it is important to understand if the accumulation of those metabolites could potentially inhibit cofactors re-oxidation and fermentation. The effects of lactate, ethanol, formate and propionate on fermentation and digestion are best studied in experiments in which those metabolites are externally added to rumen fermentation as pure compounds.…”
Section: Effects Of Dihydrogen Accumulation On the Rates Of Fermentatmentioning
confidence: 99%